2022
DOI: 10.1007/s00146-022-01548-2
|View full text |Cite
|
Sign up to set email alerts
|

Expert views about missing AI narratives: is there an AI story crisis?

Abstract: Stories are an important indicator of our vision of the future. In the case of artificial intelligence (AI), dominant stories are polarized between notions of threat and myopic solutionism. The central storytellers—big tech, popular media, and authors of science fiction—represent particular demographics and motivations. Many stories, and storytellers, are missing. This paper details the accounts of missing AI narratives by leading scholars from a range of disciplines interested in AI Futures. Participants focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Diversity is not just about fairness but is essential for creating AI systems that are unbiased, ethical, and beneficial for society (Shams, Zowghi, and Bano 2023). Thus, enhancing the diversity of AI creators is imperative to ensure that the technology reflects a broad spectrum of human experiences and values, contributing positively to societal progress (Chubb, Reed, and Cowling 2022). It is important to note that this layer of the ecosystem is closely connected with the internal dimension of AI identity.…”
Section: The Creators Of Aimentioning
confidence: 99%
“…Diversity is not just about fairness but is essential for creating AI systems that are unbiased, ethical, and beneficial for society (Shams, Zowghi, and Bano 2023). Thus, enhancing the diversity of AI creators is imperative to ensure that the technology reflects a broad spectrum of human experiences and values, contributing positively to societal progress (Chubb, Reed, and Cowling 2022). It is important to note that this layer of the ecosystem is closely connected with the internal dimension of AI identity.…”
Section: The Creators Of Aimentioning
confidence: 99%
“…that mimic human intelligence or an embodied entity that can perform physical actions (Ding et al, In review). However, AI is seen by experts closer to algorithms (McCarthy, 2007) and tools for building computer programs (Chubb et al, 2022). A widely acceptable definition of AI is the science and engineering behind the development of intelligent machines that solve problems through techniques such as machine learning, natural language processing, and reinforcement learning (Mondal, 2020).…”
Section: Conceptualize Ai Literacy Defining Artificial Intelligence L...mentioning
confidence: 99%
“…Importantly, however, while the AI narratives literature provides an analytical framework for interpreting the plurality of different LAWS imaginaries presented in the Terminator films, it is underutilised in the study of the global regulatory debates on these technologies. Much of the existing AI narratives literature has focused on cataloguing the different types of stories which have (and have not) been told about intelligent machines in the Anglophone West (Cave et al, 2019; Cave and Dihal, 2021; Chubb et al, 2022; Hudson et al, 2023). This has invited the study of how these stories circulate among different audiences including the general public (Sartori and Bocca, 2023) and AI researchers (Dillon and Schaffer-Goddard, 2022).…”
Section: Sociotechnical Imaginaries and Ai Narratives: A Framework Fo...mentioning
confidence: 99%
“…2 This is surprising given the attention paid to other popular culture franchises featuring ‘killer robots’ such as Battlestar Galactica (Buzan, 2010; Kiersey and Neumann, 2013) and these film’s perceived influence on American politics (Broxmeyer, 2010). The AI narrative literature, in contrast, has so far been principally focused on categorising the different types of stories that have and have not been told about these technologies (Cave et al, 2018; Cave and Dihal, 2019; Chubb et al, 2022; Hudson et al, 2023). While it is suggested that awareness of AI narratives may influence the governance of AI-associated technologies (Cave and Dihal, 2019: 74; Hudson et al, 2023: 198; Sartori and Bocca, 2023: 454), their circulation in the global regulatory debates on LAWS remains unexplored.…”
mentioning
confidence: 99%